2023
DOI: 10.11591/eei.v12i3.4830
|View full text |Cite
|
Sign up to set email alerts
|

Improving sentiment reviews classification performance using support vector machine-fuzzy matching algorithm

Abstract: High dimensionality in data sets is one of the challenges faced in classification, data mining, and sentiment analysis. In the data set, many dimensionalities require effort to simplify. Many of these dimensionalities have a major impact on the complexity and performance of the algorithms used for classification. Various challenges were encountered, including how to determine the optimal combination of pre-processing techniques, how to clean the dataset, and determine the best classification algorithm. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 25 publications
(94 reference statements)
2
15
0
Order By: Relevance
“…Afterward, dimensionality reduction was performed using FM and TF-IDF techniques. The classification stage employed the SVM algorithm due to its demonstrated high performance in previous studies [14]. Analysis through these stages showed that customer orientation tended to be positive with a value of 76%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, dimensionality reduction was performed using FM and TF-IDF techniques. The classification stage employed the SVM algorithm due to its demonstrated high performance in previous studies [14]. Analysis through these stages showed that customer orientation tended to be positive with a value of 76%.…”
Section: Discussionmentioning
confidence: 99%
“…The annotation process involves linguists who determine the sentiment orientation of each sentence, with 1 indicating a negative review and 2 for a positive one. It is essential to note that this process is both time-consuming and costly [14]. Some data points (examples in Table 1) may not be suitable for manual annotation, as mentioned in Section 2.…”
Section: F Measurement and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Text classification is assigning documents to predefined classes. Web page classification [1,2], sentiment classification [3][4][5], customer complaints classification [6,7], spam detection [8,9], tweet classification [10,11] and other classifications [6,[12][13][14][15][16][17][18] are samples of text classification in digital environment.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [9] proposed a hybrid model based on simulated annealing (SA) and generalized normal distribution optimizer (GNDO). Nurcahyawati et al [10] proposed a comment classification model based on SVM. Parlak et al [11] proposed a text classification feature filtering method based on machine learning.…”
Section: Introductionmentioning
confidence: 99%